2019
DOI: 10.1111/bpa.12685
|View full text |Cite
|
Sign up to set email alerts
|

Extravascular fibrinogen in the white matter of Alzheimer’s disease and normal aged brains: implications for fibrinogen as a biomarker for Alzheimer’s disease

Abstract: The blood–brain barrier (BBB) regulates cerebrovascular permeability and leakage of blood‐derived fibrinogen. Dysfunction of the BBB has been associated with cerebral arteriolosclerosis small vessel disease (SVD) and white matter lesions (WML). Furthermore, BBB dysfunction is associated with the pathogenesis of Alzheimer’s disease (AD) with the presence of CSF plasma proteins suggested to be a potential biomarker of AD. We aimed to determine if extravascular fibrinogen in the white matter was associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 59 publications
3
24
1
1
Order By: Relevance
“…RAGE is expressed on different kinds of cells in the brain, including brain capillaries. An increase in BBB permeability and the leakage of macromolecules from capillaries were observed in the postmortem brains of Alzheimer's patients [124,125] and an in-vitro BBB model [126,127]. These findings strongly imply that maintenance of the integrity of the BBB is impaired in Alzheimer's disease.…”
Section: Neurodegenerative Disease and Bbb Disruptionmentioning
confidence: 80%
“…RAGE is expressed on different kinds of cells in the brain, including brain capillaries. An increase in BBB permeability and the leakage of macromolecules from capillaries were observed in the postmortem brains of Alzheimer's patients [124,125] and an in-vitro BBB model [126,127]. These findings strongly imply that maintenance of the integrity of the BBB is impaired in Alzheimer's disease.…”
Section: Neurodegenerative Disease and Bbb Disruptionmentioning
confidence: 80%
“…[ 50 ] Nevertheless, the language disorder of the scattered CSVD is often manifested as less speech, but the understanding and expression ability are generally intact. Previous study [ 51 , 52 ] has compared the language functions of patients with AD and CSVD, and it has been found that the AD group only has showed impairment of semantic fluency, while the CSVD group has showed impaired semantic fluency and speech fluency, which may be related to the reduction of executive function and processing speed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fibrinogen promotes cognitive deficits by CD11b/CD18-mediated microglial activation of Alzheimer's disease (AD) pathogenesis ( 35 ). Furthermore, fibrinogen is a potential biomarker for multiple sclerosis and Alzheimer's disease ( 36 , 37 ). Neurons and astrocytes have been reported to have the ability to express FGA and FGB, which indicates that the FGA- and FGB-derived peptides may be involved in the HIE pathological processes and may have implications for the early diagnosis of HIE.…”
Section: Discussionmentioning
confidence: 99%